Apple allergens as affected by cultivation technolog and variental factors - Takács, K.; Szamos, J.; Szabó, E. E.; Szabó, Z.; Nyéki, J.; Gelencsér, É. (International Journal of Horticultural Science, 2010)
Our objective was to study the effect of organic farming and area of cultivation on the allergen content of apple varieties by quantification of the major allergens (Mal d 1 and Mal d 2) using allergen-specific ELISA. The obtained results showed that except Idared IX. 29. most of examined varieties, when cultivated under organic farming conditions, contained lower level of Mal d1 allergen than those produced with integrated farming. The different varieties were found to vary substantially in theirMal d 1 allergen content. Furthermore, with some varieties the area of cultivation affected to some extent the content of Mal d 1 allergen.